2017
DOI: 10.1007/s12273-017-0381-0
|View full text |Cite
|
Sign up to set email alerts
|

Cruise ships like buildings: Wayfinding solutions to improve emergency evacuation

Abstract: This research aims at demonstrating that wayfinding solutions can improve the effectiveness of the evacuation processes in complex architectural spaces such as those of cruise ships. We investigated the behaviours of passengers in maritime disaster to figure out whether people act similarly during buildings egress and ships evacuation. Data were collected through questionnaires administered in 2015 to passengers boarding various cruise ships at the port of Ancona (Italy), and through the analysis of real foota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 65 publications
(138 reference statements)
1
37
0
1
Order By: Relevance
“…To improve this, the government of the Republic of Korea confirmed that it was making efforts to enhance the seafarers' ability by amending the related national laws. However, it was confirmed by examining causes with a low performance in the survey results that simply improving the seafarers' ability to respond to emergencies was not well established [76][77][78]. In order to address this issue, the improvement of the working environment of the seafarers-who are the main subjects for implementing regulationsand employing highly qualified seafarers were confirmed to be essential [79].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To improve this, the government of the Republic of Korea confirmed that it was making efforts to enhance the seafarers' ability by amending the related national laws. However, it was confirmed by examining causes with a low performance in the survey results that simply improving the seafarers' ability to respond to emergencies was not well established [76][77][78]. In order to address this issue, the improvement of the working environment of the seafarers-who are the main subjects for implementing regulationsand employing highly qualified seafarers were confirmed to be essential [79].…”
Section: Discussionmentioning
confidence: 96%
“…This indicates that most of the technical improvements that addressed these causes before the accident were considered to have been well established. Therefore, there is an increasing need to develop relevant technology to respond to a loss of stability, mechanical issues, and evacuation after an accident [76][77][78]. Because ship accidents occur due to the complex action of various factors, they must be considered together with the cause of these problems; however, this study is limited to analysis using a questionnaire survey.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, simulation tools could be useful in predicting how different mitigation solutions could affect the virus spreading, as also remarked by previous studies on airborne diseases mitigation (Saari et al 2006;Gao et al 2008Gao et al , 2016Laskowski et al 2011;Zhang et al 2018). The importance of such tools has been evidenced in many different cases concerning individuals' safety in the built environment, including crowd conditions, such as those related to emergency safety and evacuation (Zheng et al 2009;Casareale et al 2017;Ronchi and Lovreglio 2020).…”
Section: Introductionmentioning
confidence: 92%
“…However, this method must ensure correct synchronization between agents simultaneously accessing the same location simultaneously. Casareale et al proposed wayfinding solutions and investigated the behaviors of processes in maritime disasters to determine whether people act similarly during buildings egress and ships evacuation, thereby demonstrating the effectiveness of evacuation processes in complex architectural spaces.…”
Section: Related Workmentioning
confidence: 99%
“…With the development of computer graphics and virtual reality, real‐time crowd simulation has been a major challenge. In recent years, crowd simulation has seen broad applications in, for example, computer games, movies, training simulations, safety modeling, architecture, training, urban engineering, and virtual heritage.…”
Section: Introductionmentioning
confidence: 99%